Impact of English Language Imperialism on Pakistani Learners’ Psychology - Khan, Tania Ali (Journal of Communication and Cultural Trends, 2023)
In the course of the past few years, English language has acquired uncommon consideration in Pakistan. In the progression of this momentum, students have embarked on learning and communicating in English at the cost of dismissing their native language, that is, Urdu. The current study attempted to discuss the dominance of English language and its consequences on the psychology of learners. This study addressed the question of whether students perceive English language imperialism as a threat to their national language, Urdu. The current study is quantitative in nature. A sample size comprising 100 participants was selected and those learners were studying in undergraduate and graduate programs at Kinnaird College for Women Lahore, Minhaj University, and the University of Punjab, Lahore. A self-constructed questionnaire was utilized to gather the information. Moreover, an investigation was undertaken on the impacts of the independent variable namely English language imperialism on the dependent variable namely students’ psychology. The results indicated a notable interconnection among various psychological factors, collectively exerting a significant influence on student’s psychological well-being. Since they consider it a sign of accomplishment in their academic and professional careers.